Efficacy and Safety of Glycoprotein IIb/IIIa Inhibitors on Top of Ticagrelor in STEMI: A Subanalysis of the ATLANTIC Trial - Tavenier, Anne H.; Hermanides, Renicus S.; Fabris, Enrico; Lapostolle, Frédéric; Silvain, Johanne; ten Berg, Jurrien M.; Lassen, Jens F.; Bolognese, Leonardo; Cantor, Warren J.; Cequier, Ángel; Chettibi, Mohamed; Goodman, Shaun G.; Hammett, Christopher J.; Huber, Kurt; Janzon, Magnus; Merkely, Béla; Storey, Robert F.; Zeymer, Uwe; Ecollan, Patrick; Collet, Jean-Phillipe; Willems, Frank F.; Diallo, Abdourahmane; Vicaut, Eric; Hamm, Christian W.; Montalescot, Gilles; van 't Hof, Arnoud W. J.; ATLANTIC investigators (Thrombosis and Haemostasis, 2020)
Background Glycoprotein IIb/IIIa inhibitors (GPIs) in combination with clopidogrel improve clinical outcome in ST-elevation myocardial infarction (STEMI); however, finding a balance that minimizes both thrombotic and bleeding risk remains fundamental. The efficacy and safety of GPI in addition to ticagrelor, a more potent P2Y12-inhibitor, have not been fully investigated.Methods 1,630 STEMI patients who underwent primary percutaneous coronary intervention (PCI) were analyzed in this subanalysis of the ATLANTIC trial. Patients were divided in three groups: no GPI, GPI administration routinely before primary PCI, and GPI administration in bailout situations. The primary efficacy outcome was a composite of death, myocardial infarction, urgent target revascularization, and definite stent thrombosis at 30 days. The safety outcome was non-coronary artery bypass graft (CABG)-related PLATO major bleeding at 30 days.Results Compared with no GPI (n = 930), routine GPI (n = 525) or bailout GPI (n = 175) was not associated with an improved primary efficacy outcome (4.2% no GPI vs. 4.0% routine GPI vs. 6.9% bailout GPI; p = 0.58). After multivariate analysis, the use of GPI in bailout situations was associated with a higher incidence of non-CABG-related bleeding compared with no GPI (odds ratio [OR] 2.96, 95% confidence interval [CI] 1.32–6.64; p = 0.03). However, routine GPI use compared with no GPI was not associated with a significant increase in bleeding (OR 1.78, 95% CI 0.88–3.61; p = 0.92).Conclusion Use of GPIs in addition to ticagrelor in STEMI patients was not associated with an improvement in 30-day ischemic outcome. A significant increase in 30-day non-CABG-related PLATO major bleeding was seen in patients who received GPIs in a bailout situation.
Keywords: glycoprotein IIb/IIIa inhibitors; primary percutaneous coronary intervention; STEMI; ticagrelor; bailout; tirofiban; eptifibatide; abciximab